SUSTAINABLE TOURISM AS A MEANS OF DOWNSHIFTING IN THE CONTEXT OF REALIZING A SUCCESSFUL PERSONALITY: A METHODOLOGICAL APPROACH - Козьменко, Олена; Зеленко, Олена (SWorldJournal, 2025)
In the contemporary context of the global ecological crisis, social conflicts, and pandemic and wartime challenges, the need to rethink the consumer behavior model is intensifying. An increasing number of people are seeking alternatives to the race for ma